Analisis Kematangan Tata Kelola Sistem Informasi Pelayanan Publik Berdasarkan Framework COBIT 2019 pada Dinas Kependudukan dan Pencatatan Sipil Kota Medan - Oktaviana Bangun; Anggita Wulandary Lubis; Esta Uly Br Pasaribu; Yehezkiel Kristian Albonar Pardede; Emia Br Ginting; Bryan Agustinus Sihombing (Universitas Mandiri Bina Prestasi, 2026)
This study uses the COBIT 2019 approach to assess the maturity of the public service information system (IS) governance at the Medan City Population and Civil Registration Agency (Disdukcapil). The assessment focuses on processes DSS01 (Service Request and Incident Management) and DSS06 (Business Process Governance) to ensure the quality of digitally-based public services. Analysis targets include e-government service quality, citizen data integrity, queue performance, and system downtime. The research methodology employs quantitative and qualitative case studies, including a capability maturity questionnaire (n=50), structured interviews (n=6), and aggregated data on operational incidents over a three-month period based on global benchmarking standards. The analysis results showed an average maturity score of 2.84 (Managed) for DSS01 and 2.57 (Managed) for DSS06, indicating that IT processes are implemented and documented, but lack standardization across the organization. The largest gaps were identified in service-level agreements (SLAs) and incident escalation criteria, as well as data integrity reconciliation mechanisms. Findings from operational data indicate that while technical controls for data integrity exist, the lack of formal audit trails and periodic system downtime significantly impact service reliability. Recent global trends in system outages highlight the importance of robust mitigation strategies to prevent service disruptions. The study presents strategic recommendations organized into a 12-month roadmap: (1) strengthening the service desk and formalizing SLAs; (2) implementing a data change audit trail; (3) developing automated validation and reconciliation procedures; and (4) improving capacity planning to mitigate downtime. These findings are crucial for aligning IT operations with national and global goals of providing fast, accurate, and transparent public services.